The Effect of Product, Price and Promotion on Purchase Decision-Mediated by Customer Satisfaction of Oriflame M3 Network Community - Sugiono, Edi; Sri Widiastutik (Open Access Indonesia Journal of Social Sciences, 2021)
This study was aimed to analyse the effect of product, price, promotion, customer satisfaction, purchase decision. The study participant was 125 people. data were collected by questionnaires and structural equation model (SEM) were applies as an analysis technique. The results analysis showed that product quality, price, personal selling have positive and significant effect on the customer satisfaction and customer loyalty. The implication is product quality, price, personal selling need to be increased in order to customer satisfaction and customer loyalty.